Heavy metal content in pumpkin pond of Kutaraja Fishing Port Banda Aceh - Muhammad Muhammad; Shelly Anggi Pratiwi; Thaib Rizwan; Zulkarnain Jalil (Depik, 2021)
Fishing port scan support fishery resources management by incorporating social-economic activities to improve the local community's welfare; however, it can also negatively impact the environment by increasing waste pollution to the surrounding waters. Kutaraja Fishing Port, Banda Aceh, is one of the active fishing ports that conduct multiple activities, such as industrials, transportations, and domestic activities threatening the environment through the production of pollution such as heavy metals. The purpose of this study is to determine the concentration of heavy metals Zinc (Zn) and Chromium (Cr) and the sediment contamination level in the Kutaraja Fishing Port, Banda Aceh. This research was conducted in February 2021 at the water site of Samudra Kutaraja Fishing Port, Banda Aceh, and sampled sediments using the purposive sampling method. Samples were then analyzed for heavy metal concentration using the Atomic Absorption Spectrophotometer (AAS) instrument in the laboratory of the Aceh Industrial Research and Standardization Center (BARISTAND). The results showed that the concentration of heavy metal Zn ranged from 15.6507 - 27.2939 mg/kg. The majority of heavy metal Cr concentrations were below the test limit of 0.000, except at station 2, which was 9.1212. Both heavy metal concentrations are still categorized as low contamination criteria and still below the Australian and New Zealand Environment and Conservation Council (ANZECC, 2000) and the Canadian Council of Ministers for the Environment (CCME, 2002). This research proved that both heavy metals do not threaten the biota and have a low contamination level in the waters.Keywords:SedimentHeavy metal (Zn)Heavy metal (Cr)Atomic-absorptionSpectro-photometerAssessment